Foot strike patterns and ground contact times during high-calibre middle-distance races - Hayes, P.; Caplan, N. (Journal of Sports Sciences, 2012)
The aims of this study were to examine ground contact characteristics, their relationship with race performance, and the time course of any changes in ground contact time during competitive 800 m and 1500 m races. Twenty-two seeded, single-sex middle-distance races totalling 181 runners were filmed at a competitive athletics meeting. Races were filmed at 100 Hz. Ground contact time was recorded one step for each athlete, on each lap of their race. Forefoot and midfoot strikers had significantly shorter ground contact times than heel strikers. Forefoot and midfoot strikers had significantly faster average race speed than heel strikers. There were strong large correlations between ground contact time and average race speed for the women's events and men`s 1500 m (r = -0.521 to -0.623; P < 0.05), whereas the men's 800 m displayed only a moderate relationship (r = -0.361; P = 0.002). For each event, ground contact time for the first lap was significantly shorter than for the last lap, which might reflect runners becoming fatigued.